Meningkatkan Kreativitas Anak Di Desa Bandar Magodang Melalui Kegiatan Festival Anak - Hajar Marhani; Lidya Lidya; Auliya Amanda; Ziviska Vani (Jurnal Pengabdian Masyarakat Nusantara, 2023)
Community Service (PEMA) of the North Sumatra State Islamic University is one of the activities in Bandar Magodang Village. This children’s festival program is implemented to increase children’s self-confidence and creativity. The method for this children’s festival is the provision, training and practice method. 26 students were involved in the Bandar Magodang village sports hall. The children’s festival will be held on August 16 2023. In this activity there are 4 competition categories including coloring competition, call to prayer competition, short surah memorization competition and fashion show competition. This activity was attended by 52 children who were divided into 4 competition categories, namely a coloring competition for 10 children, an adhan competition for 6 children, a short surah memorization competition for 28 people and a Muslim fashion competition for 10 children. The Soleh Children’s Festival received a very good response from the people of Bandar Magodang village, because it is a very educational activity for children in Bandar Magodang village, especially in helping to increase children’s Islamic knowledge and self-confidence.